2000
DOI: 10.1089/10430340050016274
|View full text |Cite
|
Sign up to set email alerts
|

Transient Production of Bone Morphogenetic Protein 2 by Allogeneic Transplanted Transduced Cells Induces Bone Formation

Abstract: The aim of this study was to evaluate the use of transplantation of genetically modified allogeneic cells as a method to induce bone formation. In this study, we infected a murine osteoprogenitor cell line with a retroviral vector containing the human bone morphogenic protein 2 (BMP2) gene. Transduced cells exhibited more alkaline phosphatase activity than cells treated with any of the tested doses of recombinant human BMP2 protein (rhBMP2). The transduced cells were suspended in a collagen solution and inject… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
38
1

Year Published

2001
2001
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(40 citation statements)
references
References 30 publications
1
38
1
Order By: Relevance
“…The cells, once transduced with Ad-BMP2 act primarily as a source of local BMP2, regardless of their osteogenic potential. Similarly, Engstrand et al 7 have recently demonstrated that retrovirally transduced W20-17 cells, a mouse bone marrow cell line, showed significant bone formation; however, the cells were rapidly cleared even in the presence of a collagen carrier.…”
Section: Discussionmentioning
confidence: 78%
See 1 more Smart Citation
“…The cells, once transduced with Ad-BMP2 act primarily as a source of local BMP2, regardless of their osteogenic potential. Similarly, Engstrand et al 7 have recently demonstrated that retrovirally transduced W20-17 cells, a mouse bone marrow cell line, showed significant bone formation; however, the cells were rapidly cleared even in the presence of a collagen carrier.…”
Section: Discussionmentioning
confidence: 78%
“…[1][2][3][4][5][6][7][8] Localized delivery of cells transduced ex vivo with adenoviral vectors encoding bone morphogenetic proteins (BMPs) has proven successful in induction of new bone formation in hetero-and orthotopic locations. Although safe and efficacious gene-based bone induction systems have yet to be developed, the adenoviral delivery of BMP offers the potential of rapidly achieving local effective concentrations of the protein to induce bone formation.…”
Section: Introductionmentioning
confidence: 99%
“…Although there are several studies which have shown evidence for skeletal regeneration in vivo using ex vivo modified stromal cells, myoblasts, or fibroblasts, 10,15,16,22,24,25 our study is unique in that it provides quantitative data on the extent of healing by valid bone density measurements. Furthermore, our data demonstrate that the healing of a critical calvarial defect is dependent on the time of exposure, as well as the number of BMP4-expressing stromal cells implanted.…”
Section: Bmp4-producing Cells Were Identified By Immunostaining (Browmentioning
confidence: 99%
“…Regional gene transfer may therefore provide a viable alternative to protein therapy. Recently, different gene therapy approaches to bone regeneration have been studied, suggesting the use of viral vectors such as adenoviruses [10][11][12][13][14][15][16][17] and retroviruses 18,19 as carriers of BMP-2 cDNA. Adenoviruses, although highly immunogenic and at higher doses toxic to several tissues, are generally considered as the most efficient gene transfer vehicles.…”
Section: Introductionmentioning
confidence: 99%